TETRODOTOXIN (TTX) IN GOBY YONGEICHTHYS NEBULOSUS (FORSKAL 1775) COLLECTED FROM KHANH HOA PROVINCE - Ha, Dao Viet; Nga, Do Tuyet (Vietnam Journal of Marine Science and Technology, 2006)
TETRODOTOXIN (TTX) IN GOBY YONGEICHTHYS NEBULOSUS (FORSKAL 1775) COLLECTED FROM KHANH HOA PROVINCE